Immunodetection of heat shock protein 70 and cell death in liver of a neotropical fish acutely and chronically exposed to acetaminophen and propranolol - Pereira, Beatriz Vieira Ramos (2022)
The use of pharmaceutical drugs ends frequently in their inappropriate disposal and treatment at waste water treatment plants, which is the cause of their widespread presence in the environment. Yet, there is limited understanding or knowledge of their effects to non-target aquatic organisms. The drugs acetaminophen (analgesic and antipyretic) and propranolol (β-blocker) are widely found in the aquatic environment, where they can interact with non-target exposed organisms, causing adverse effects. Heat shock proteins (namely HSP70) are molecular chaperones which help to refold misfolded cellular proteins, and the increase in their in vivo levels indicates a change in the cell to counteract the proteotoxic effects of the triggered stress, namely which is consequent to exposure to toxicants. The objective of this study was to quantify the levels of liver HSP70 proteins in individuals of the neotropical fish species Phalloceros harpagos, acutely and chronically exposed to concentrations of acetaminophen and propranolol, in the range of those already determined to occur in the wild. Fish acutely exposed to acetaminophen (concentrations of 8, 80, 800, and 8000 μg L-1) and to propranolol (levels of 1, 10, and 1000 μg L-1) evidenced increased intensity of HSP70 immunolabeling in liver cells. Similarly, animals chronically exposed to propranolol, at concentrations of 0.0625, 0.125, 0.25, and 0.5 μg L-1, showed a comparable trend. This finding suggests the triggering of a cytoprotective effect that was effective in preventing cell death in exposed groups in relation to the control group. In contrast, chronic exposure to acetaminophen caused a decrease in HSP70 labeling intensity in fish hepatocytes (animals exposed to 5, 10, 20, 40, and 80 μg L-1), with no induction of DNA fragmentation in the nuclei of hepatocytes of these fish. Some of the hepatic HSP70 responses observed in this study were obtained at levels already reported to occur in the wild. Finally, this study showed how levels of acetaminophen at microliter concentration can exert side effects on non-target organisms after chronic exposure, suggesting that environmentally exposed organisms may be subjected to adverse conditions that modify the typical response pattern of HSP70 levels.